BRAF V600E expression and distribution in desmoplastic infantile astrocytoma/ganglioglioma - Kölsche, Christian; Sahm, Felix; Paulus, W.; Mittelbronn, M.; Giangaspero, F.; Antonelli, M.; Meyer, Jochen; Lasitschka, Felix; Deimling, Andreas von; Reuss, David (Neuropathology & applied neurobiology, 2014)
Desmoplastic infantile astrocytoma/ganglioglioma (DIA/DIG) is a rare primary neuroepithelial brain tumour typically affecting paediatric patients younger than 24 months. Knowledge about genetic alterations in DIA/DIG is limited. However, a previous study on BRAF V600E mutation in paediatric glioma revealed a BRAF mutation in one of two tested DIAs/DIGs. The limited number of cases in that study did not allow any conclusion about mutation frequency of BRAF in this tumour entity.
First published: 04 July 2013
Gesehen am 18.09.2020